Cargo securement handbook for drivers (J.J. Keller & Associates, 2007)
" ... A field guide and reference for securing cargo on commercial motor vehicles according to the standards in effect in both the United States and Canada"--Page 1.
Keywords: Truck driving -- Safety measures -- Handbooks, manuals, etc.; Cargo handling -- Handbooks, manuals, etc.; Freight and freightage -- Safety measures -- Handbooks, manuals, etc.; Straps -- Handbooks, manuals, etc.; elektronické knihy; electronic books